State of the Art Auction '96 : Catalogue of Works. - Thurber, Garth (Vancouver : Vancouver Art Gallery Vancouver, 1996)
Aspell, Peter ; Smith, Gordon ; Dupuis, Lorenzo ; Arnoldi, Charles ; Douglas, Stan ; Lam, Sam ; Lukacs, Attila Richard ; Gillmore, Graham ; Craven, David ; Chihuly, Dale ; Kirton, Douglas ; Yamagata, Hiro ; Warhol, Andy ; Rogers, Otto ; Xiong, Gu ; Goodwin, Betty ; Hart, Jim ; Kipling, Ann ; Plaskett, Joe ; Evrard, Jamie ; Gaskin, Mark ; Service, Pat ; Hardy, Greg ; Pratt, Mary ; Iskowitz, Gershon ; Sterbak, Jana ; Tanare, Takao ; Kirton, Douglas ; Bierk, David ; Falk, Gathie ; Gorenko, Rick ; Ruscha, Edward ; Blackwood, David ; Prince, Richard ; Koerner, John ; Graham, Rodney ; Smith, Gordon ; Young, Jason ; Switzer, Allan ; Davis, Fred ; Marshall, Vicky ; Bush, Jack ; Keeley, Shelagh ; Shaffer, Drew ; Yuxweluptun, Lawrence Paul ; Graham, Rodney ; Graham, Robert ; Schmidt, Marianna ; Brackman-Sharp, Judith ; McWilliams, Al ; Neil, Al ; Fouquet, Monique ; Mentor, Will ; Penny, Evan ; Geleynse, Wyn ; Cran, Chris
biografie
Engels
boek